COHORT METHOD: STATISTICAL AND DESIGN FOUNDATIONS – AN ANALYTICAL OVERVIEW - Samadov Firdavs Furqatkhoja ogli (TADQIQOTLAR, 2025)
Summary: The cohort method represents one of the most significant analytical approaches in epidemiological research, providing a high degree of reliability in establishing cause-and-effect relationships. This article analyzes the fundamental design principles of the cohort method, key statistical indicators, and their mechanisms of application within the research process. Differences between prospective and retrospective cohort studies, as well as their respective advantages and limitations, are discussed. Furthermore, methods for calculating statistical indicators such as relative risk (RR) and attributable risk (AR), along with their epidemiological interpretation, are described. The paper also highlights the practical applications of the cohort method, particularly its importance in studying chronic and infectious diseases. The analysis demonstrates that the cohort method serves as a crucial scientific basis for an in-depth examination of factors influencing disease development, assessing risk levels, and developing preventive strategies.